Does inequality promote employment? An international comparison - Sonja Jovicic; Ronald Schettkat (University of Wuppertal, Schumpeter School of Business and Economics, 2013)
This paper investigates whether the 'big tradeoff' between efficiency and inequality exists, and analyzes empirically the relationship between inequality, redistribution, and employment/unemployment. The analysis is based on a cross-country longitudinal data set (panel data) of 21 OECD countries in the period 1980 to 2010. We use inequality and redistribution measures (output indicators) rather than institutional variables (input indicators) as independent variables. We do not find a significant effect of income and wage distribution on labor market performance and cannot confirm the hypothesized 'big tradeoff'.
urn:nbn:de:hbz:468-20131223-105422-4
Keywords: 330